Neodymium-iron-boron magnet two-dimensional composite corrosion-resistant coating and preparation method thereof

By preparing a two-dimensional composite corrosion-resistant coating of NdFeB magnet on the surface of NdFeB magnets, and ion exchange electrodeposition is performed using nickel-based plating solution, complexing agent and two-dimensional Ti3C2Tx, the problem of insufficient corrosion resistance of NdFeB magnets is solved, and higher corrosion resistance and coating flatness are achieved.

CN119710867AActive Publication Date: 2025-03-28JIANGXI UNIV OF SCI & TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411655695.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The corrosion resistance of neodymium iron boron rare earth permanent magnet materials is insufficient, especially in the field of new energy vehicles, resulting in a short service life.

Method used

By preparing a two-dimensional composite corrosion-resistant coating of NdFeB magnet on the surface of NdFeB magnet, a nickel-based plating solution, complexing agent and two-dimensional Ti3C2Tx are used to synergize electrostatic assembly and pulsed electric field to form a corrosion-resistant composite coating.

Benefits of technology

The corrosion resistance of the electrodeposited plating layer on the surface of the neodymium iron boron magnet is significantly improved, the agglomeration problem caused by adsorption of two-dimensional materials with metal cations in solution is avoided, and the flatness and corrosion resistance of the plating layer are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710867A_ABST
    Figure CN119710867A_ABST
Patent Text Reader

Abstract

The invention provides a neodymium-iron-boron magnet two-dimensional composite corrosion-resistant coating and a preparation method thereof, and belongs to the technical field of rare earth permanent magnet material coating preparation. The method comprises the following steps: pretreating a neodymium-iron-boron magnet to prepare a to-be-electroplated magnet with a clean and rough surface; a to-be-electroplated magnet is soaked in the deposition liquid, a pulsed electric field is applied for ion exchange electrodeposition, and a two-dimensional composite coating is deposited on the surface of the to-be-electroplated magnet under the synergistic effect of electrostatic assembly and the pulsed electric field; wherein the deposition liquid comprises a nickel-based electroplating liquid, a complexing agent and two-dimensional Ti < 3 > C < 2 > T < x >; the complexing agent is selected from ammonia water, EDTA-2Na (Ethylene Diamine Tetraacetic Acid-2Na) or ammonium citrate. The invention provides a method for applying two-dimensional Ti3C2Tx to an alloy coating, and the corrosion resistance of an electro-deposition coating on the surface of a neodymium-iron-boron magnet is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth permanent magnet material coating preparation, and particularly relates to a two-dimensional composite corrosion-resistant coating of a neodymium iron boron magnet and a preparation method thereof. Background Art

[0002] Neodymium iron boron permanent magnets are known as the "king of magnets" for their excellent magnetic properties. They not only have excellent properties such as high magnetic energy product and high cost performance, but are also easy to process into various sizes. Therefore, they are widely used in aerospace, wind power generation, energy-saving home appliances, electronic appliances, and new energy vehicles. However, due to its special multi-phase structure and the differences in chemical properties between the phases, neodymium iron boron rare earth permanent magnet materials exhibit inherent insufficient corrosion resistance. Especially in the field of new energy vehicles, the service life of automotive motors is often more than ten years, which puts higher demands on the corrosion resistance of neodymium iron boron rare earth permanent magnet materials. At present, a major strategy to improve the corrosion resistance of neodymium iron boron rare earth permanent magnet materials is to improve the corrosion resistance by adding corrosion-resistant two-dimensional materials to the surface protective layer. Studies have shown that Ti3C2T x As a corrosion-resistant two-dimensional material, it can effectively improve the corrosion resistance of corrosion-resistant composite coatings. However, this type of material is rarely used in the modification of alloy electroplating layers. The main reason is that the material is easily adsorbed with metal cations in the solution, resulting in material agglomeration, which reduces the corrosion resistance of the final coating. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a two-dimensional composite corrosion-resistant coating for NdFeB magnets and a preparation method thereof, aiming to solve at least one technical problem in the background technology.

[0004] The present invention is achieved in that:

[0005] The present invention provides a method for preparing a two-dimensional composite corrosion-resistant coating of a neodymium iron boron magnet, the method comprising the following steps:

[0006] Pre-treating the NdFeB magnets to obtain magnets with clean and rough surfaces to be electroplated;

[0007] The magnet to be electroplated is immersed in a deposition solution, and a pulsed electric field is applied to perform ion exchange electrodeposition, so that a two-dimensional composite coating is deposited on the surface of the magnet to be electroplated under the synergistic effect of electrostatic assembly and pulsed electric field;

[0008] The deposition solution includes a nickel-based electroplating solution, a complexing agent and a two-dimensional Ti3C2T x ; The complexing agent is selected from ammonia water, EDTA-2Na or ammonium citrate.

[0009] Furthermore, the preparation method of the deposition solution is: adding a complexing agent to a nickel-based electroplating solution, adjusting the solution pH to 4-6 after sufficient reaction, and then adding Ti3C2T x powder and dispersed it by ultrasonic to obtain a deposition solution.

[0010] Furthermore, the two-dimensional Ti3C2T x The addition amount is 0.1g / L~0.3g / L.

[0011] Furthermore, when the complexing agent is ammonia water, its usage is 5ml / L to 20ml / L; when the complexing agent is EDTA-2Na or ammonium citrate, its usage is 0.2g / L to 2g / L.

[0012] Furthermore, the nickel-based electroplating solution includes the following components in mass concentrations: 180 g / L to 280 g / L of nickel sulfate; 20 g / L to 40 g / L of nickel chloride; 30 g / L to 40 g / L of boric acid; and 0.05 g / L to 0.1 g / L of sodium dodecyl sulfate.

[0013] Furthermore, the NdFeB magnet pretreatment specifically includes:

[0014] First, place the NdFeB magnet in an alkaline cleaning solution at 65°C ± 5°C, stir to remove oil stains from the NdFeB magnet, and then clean it with water; the alkaline cleaning solution includes NaOH, Na2CO3, Na3PO4, an emulsifier and sodium dodecyl sulfate;

[0015] Then soak the NdFeB magnet in HNO3 solution for 30s±5s, and then clean it with water;

[0016] Then, the NdFeB magnet is immersed in the H2SO4 solution for 30s±5s, cleaned with water and then ultrasonically cleaned with anhydrous ethanol to obtain a magnet to be electroplated with a clean and rough surface.

[0017] Furthermore, the parameters of ion exchange electrodeposition are: forward current density is 5A / dm 2 ~15A / dm 2 , operating frequency is 400Hz~1000Hz, duty cycle is 20%~60%; reverse current density is 0A / dm 2 ~1A / dm 2 , the operating frequency is 400Hz~1000Hz, and the duty cycle is 20%~60%.

[0018] Furthermore, the temperature of the ion exchange electrodeposition is 45±5°C.

[0019] The present invention also provides a two-dimensional composite corrosion-resistant coating of a NdFeB magnet prepared by the above-mentioned preparation method.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention provides a two-dimensional Ti3C2T x The method applied to alloy plating further improves the corrosion resistance of the electro-deposited coating on the surface of NdFeB magnets.

[0022] 2. The present invention adds a complexing agent and a two-dimensional Ti3C2T x , Ti3C2T x Electrostatic assembly with metal ions ionized on the magnet surface, Ni 2+ Preferentially form a stable complex with the complexing agent to avoid Ti3C2T x Adsorption with the plating solution causes agglomeration.

[0023] 3. The present invention uses electrostatic assembly and ion exchange electrodeposition to prepare a composite coating with strong corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 These are SEM images of the two-dimensional composite coatings prepared in Example 1, Example 4, Example 5 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] A method for preparing a two-dimensional composite corrosion-resistant coating of a neodymium iron boron magnet, the method comprising the following steps S11-S113:

[0027] S11. First, place the NdFeB magnet in an alkaline cleaning solution at 65℃±5℃, stir to remove the oil stains on the NdFeB magnet, and then rinse it with water; the alkaline cleaning solution includes NaOH, Na2CO3, Na3PO4, an emulsifier and sodium dodecyl sulfate; then, soak the NdFeB magnet in an HNO3 solution for 30s±5s, and then rinse it with water; then, soak the NdFeB magnet in an H2SO4 solution for 30s±5s, rinse it with water, and then ultrasonically clean it with anhydrous ethanol to obtain a magnet with a clean and rough surface to be electroplated.

[0028] S12, immersing the magnet to be electroplated in a deposition solution, applying a pulsed electric field to perform ion exchange electrodeposition, and depositing a two-dimensional composite coating on the surface of the magnet to be electroplated under the synergistic effect of electrostatic assembly and pulsed electric field; wherein the deposition solution comprises a nickel-based electroplating solution, a complexing agent, and a two-dimensional Ti3C2T xThe deposition solution preparation method is as follows: add a complexing agent to the nickel-based electroplating solution, adjust the solution pH after sufficient reaction, and then add Ti3C2T x powder, and disperse by ultrasonication to obtain a deposition liquid;

[0029] When the complexing agent is ammonia water, the mass concentration of ammonia content in ammonia water is generally 60%, and the amount of ammonia water is 5ml / L to 20ml / L, for example, 5ml / L, 10ml / L, 20ml / L; but not limited to the listed values, other values ​​not listed in the numerical range are also applicable; when the complexing agent is EDTA-2Na or ammonium citrate, the amount is 0.2g / L to 2g / L, for example, 1.2g / L; but not limited to the listed values, other values ​​not listed in the numerical range are also applicable;

[0030] Ti3C2T x The amount of powder added is 0.1 g / L to 0.3 g / L, for example, 0.1 g / L, 0.2 g / L, 0.3 g / L; but not limited to the listed values, other values ​​not listed within the numerical range are also applicable;

[0031] The pH value of the deposition liquid is controlled to be 4 to 6, for example, it can be 4, 5, or 6; but it is not limited to the values ​​listed, and other values ​​not listed within the numerical range are also applicable;

[0032] The nickel-based electroplating solution may be any nickel-containing electroplating solution that can form a corrosion-resistant coating as permitted in the art. Preferably, the nickel-based electroplating solution includes the following components in mass concentrations: 180 g / L to 280 g / L of nickel sulfate; 20 g / L to 40 g / L of nickel chloride; 30 g / L to 40 g / L of boric acid; 0.05 g / L to 0.1 g / L of sodium dodecyl sulfate; for example, 220 g / L of nickel sulfate; 30 g / L of nickel chloride; 35 g / L of boric acid; and 0.08 g / L of sodium dodecyl sulfate, but the values ​​listed are not limited thereto, and other values ​​not listed within the numerical range are also applicable.

[0033] The temperature of ion exchange electrodeposition is 45±5°C; the reaction parameters are: forward current density is 5A / dm 2 ~15A / dm 2 , operating frequency is 400Hz~1000Hz, duty cycle is 20%~60%; reverse current density is 0A / dm 2 ~1A / dm 2 , the operating frequency is 400Hz~1000Hz, and the duty cycle is 20%~60%. For example, the forward current density can be 8A / dm 2 , operating frequency is 800Hz, duty cycle is 40%; reverse current density is 0.2A / dm 2, the operating frequency is 400 Hz, and the duty cycle is 20%, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0034] This method uses two-dimensional Ti3C2T x As a reinforcing phase of Ni-based coating, the corrosion resistance of commercial magnets is significantly improved. x The surface has rich functional groups and has good dispersion in the plating solution. The electrostatic assembly synergistic electric field enhancement technology adopted in this method makes the Ni in the plating solution 2+ Preferentially form a stable complex with the complexing agent to regulate Ti3C2T x with Ni 2+ The electrostatic effect of the electric field can realize the controllable Ni and Ti3C2T x Preparation of composite coatings.

[0035] S13. After the ion exchange electrodeposition is completed, the NdFeB magnet is taken out, cleaned with water and dried to obtain a NdFeB magnet with a corrosion-resistant coating formed on the surface.

[0036] Example 1

[0037] A method for preparing a two-dimensional composite corrosion-resistant coating of a neodymium iron boron magnet, using an unmagnetized N40 commercial sintered neodymium iron boron magnet as a prepared magnet, specifically comprising the following steps:

[0038] 1. Prepare the deposition solution: First, prepare the nickel-based electroplating solution according to 220 g / L nickel sulfate, 30 g / L nickel chloride, 35 g / L boric acid, and 0.08 g / L sodium dodecyl sulfate; add 60% ammonia water and adjust the pH value to 4 with sulfuric acid, stir for 10 minutes to allow the nickel ions to fully complex (ammonia water and sulfuric acid will react to form ammonium sulfate, and ammonium ions also play a complexing role); then add the monolithic Ti3C2T x The two-dimensional material is ultrasonically dispersed to form a deposition solution. The amount of ammonia water added as the complexing agent is 10 ml / L. x 0.2g / L;

[0039] 2. Pretreatment of NdFeB magnets: Place the magnets in an alkaline washing solution at 65℃±5℃ and stir to remove oil for 10 minutes. The alkaline washing formula is NaOH 7.5g / L, Na2CO3 45g / L, Na3PO4 50g / L, emulsifier OP-10 2g / L; sodium dodecyl sulfate 0.2g / L. After cleaning and removing oil, rinse with deionized water, soak in 6wt% HNO3 solution for 30s, and then rinse with deionized water; soak in 3wt% H2SO4 solution for 30s, and then ultrasonically clean with anhydrous ethanol for 3 minutes to obtain the pretreated sintered NdFeB magnets;

[0040] 3. Place the sintered NdFeB magnet pretreated in step 2 into the deposition solution prepared in step 1 to make Ti3C2T x Electrostatic assembly with metal ions ionized on the surface of the magnet; at the same time, the magnet is connected to the negative electrode, the graphite sheet is used as the positive electrode, the electrolyte temperature is controlled at 45℃±5℃, and a pulsed electric field is applied. The parameters of the pulsed electric field are: current density 8A / dm 2 , the operating frequency is 600 Hz, the duty cycle is 40%, and the processing time is 20 min, so that the magnet deposits a two-dimensional composite coating under the synergistic effect of electrostatic assembly and pulsed electric field.

[0041] 4. Finally, the sintered NdFeB magnet with nickel plating on the surface was washed in 50℃ deionized water and then dried in 60℃ environment. The SEM image of the two-dimensional composite coating after drying is as follows: Figure 1 As shown in (a).

[0042] Example 2

[0043] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that the amount of ammonia water added in Step 1 is 5 ml / L, and the other parameters and conditions are the same as those in Embodiment 1.

[0044] Example 3

[0045] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that the amount of ammonia water added in Step 1 is 20 ml / L, and the other parameters and conditions are the same as those in Embodiment 1.

[0046] Example 4

[0047] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that: the Ti3C2T x The SEM image of the two-dimensional composite coating prepared in this embodiment 4 is as follows: Figure 1 As shown in (b).

[0048] Example 5

[0049] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that: the Ti3C2T x The SEM image of the two-dimensional composite coating prepared in this embodiment 5 is as follows: Figure 1 As shown in (c).

[0050] Example 6

[0051] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that the complexing agent in Step 1 is EDTA-2Na in an amount of 1.2 g / L, and the other parameters and conditions are the same as those in Embodiment 1.

[0052] Example 7

[0053] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that the complexing agent in Step 1 is ammonium citrate in an amount of 1.2 g / L, and the other parameters and conditions are the same as those in Embodiment 1.

[0054] Example 8

[0055] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that when preparing the deposition liquid in Step 1, the pH value is adjusted to 5, and the other parameters and conditions are the same as those in Embodiment 1.

[0056] Example 9

[0057] This embodiment provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Embodiment 1 only in that when preparing the deposition liquid in Step 1, the pH value is adjusted to 6, and the other parameters and conditions are the same as those in Embodiment 1.

[0058] Comparative Example 1

[0059] This comparative example provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Example 1 only in that no complexing agent is included in step 1, and the remaining parameters and conditions are the same as those in Example 1.

[0060] Comparative Example 2

[0061] This comparative example provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Example 1 only in that: in step 1, there is no complexing agent and Ti3C2T x , the other parameters and conditions are the same as those in Example 1, and the SEM image of the obtained two-dimensional composite coating is as follows Figure 1 As shown in (d).

[0062] Comparative Example 3

[0063] This comparative example provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Example 1 only in that: the Ti3C2T x The other parameters and conditions are the same as those in Example 1.

[0064] Comparative Example 4

[0065] This comparative example provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Example 1 only in that when preparing the deposition liquid in step 1, the pH value is adjusted to 3, and the other parameters and conditions are the same as those in Example 1.

[0066] Comparative Example 5

[0067] This comparative example provides a method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet, which differs from Example 1 only in that when preparing the deposition liquid in step 1, the pH value is adjusted to 7, and the other parameters and conditions are the same as those in Example 1.

[0068] At room temperature, the electrochemical properties of the NdFeB magnets prepared in Examples 1 to 9 and Comparative Examples 1 to 5 were tested in a 3.5% NaCl solution using an electrochemical workstation. The results are shown in Table 1.

[0069] Table 1

[0070] <![CDATA[R ct (Ω·cm 2 )]]> <![CDATA[E corr (mV)]]> <![CDATA[I corr (10 -6 A·cm -2 )]]> Example 1 14354 -474 5.13 Example 2 11352 -569 10.37 Example 3 24140 -442 4.40 Example 4 9198 -587 20.13 Example 5 5308 -653 16.56 Example 6 3217 -717 54.77 Example 7 16136 -708 49.69 Example 8 9740 -476 5.36 Example 9 9297 -439 9.54 Comparative Example 1 4201 -530 7.89 Comparative Example 2 1892 -831 43.12 Comparative Example 3 3147 -711 31.01 Comparative Example 4 4125 -704 28.93 Comparative Example 5 6314 -769 13.71

[0071] Self-corrosion potential E corr The more negative, the higher the activity, and the faster the electrochemical corrosion; the corrosion rate and the self-corrosion current density I corr The larger the self-corrosion current density is, the faster the electrochemical corrosion will be. The coating impedance value is proportional to the charge transfer resistance R in the equivalent circuit. ct The greater the impedance value, the better the corrosion resistance of the coating.

[0072] From the data in Table 1, it can be seen that the self-corrosion potential E of the NdFeB magnets prepared in Examples 1 to 9 of the present invention is corr Increase, self-corrosion current density I corr Reduce the charge transfer resistance R ct The increase indicates that the coating obtained by electroplating with the deposition solution of the embodiment of the present invention has excellent corrosion resistance.

[0073] The difference between Example 1 and Example 3 is that the amount of the complexing agent ammonia water is adjusted. From the data in Table 1, it can be seen that with the increase of the complexing agent, the charge transfer resistance R ct First increase, self-corrosion potential E corr Continuously increasing, the self-corrosion current density I corr It first decreases significantly and then increases slightly; however, the overall corrosion resistance is better than that of the coating produced by conventional electrodeposition.

[0074] The difference between Example 1, Example 4 and Example 5 is that the Ti3C2T x As shown in Table 1, with the increase of Ti3C2T x The increase in charge transfer resistance R ctThe self-corrosion potential E corr Increase and decrease, the self-corrosion current density I corr First decrease and then increase; in terms of corrosion resistance, Example 1> Example 4> Example 5, but the overall corrosion resistance is better than that of the coating obtained by conventional electrodeposition. Figure 1 As shown in (a), (b) and (c), when Ti3C2T x The two-dimensional composite coating obtained when the dosage is 0.2 g / L (Example 1) has the best flatness, followed by Example 4 (Ti3C2T x The dosage is 0.1 g / L), Example 5 (Ti3C2T x The two-dimensional composite coating obtained by using the embodiment 4 (with an amount of 0.3 g / L) has more small protrusions, and its flatness is inferior to that of embodiment 4, that is, in terms of flatness, embodiment 1> embodiment 4> embodiment 5, which is consistent with the corrosion resistance effect.

[0075] The difference between Example 6 and Example 7 and Example 1 is that the complexing agent is replaced with EDTA-2Na or ammonium citrate, respectively. It can be seen from the data in Table 1 that the corrosion resistance of the deposition liquid coating using the complexing agent is good.

[0076] The difference between Example 8 and Example 9 and Example 1 is that the pH value of the deposition solution during preparation is adjusted. From the data in Table 1, it can be seen that as the pH value increases, the charge transfer resistance R ct First increase and then decrease, the self-corrosion potential E corr Decrease, self-corrosion current density I corr rise.

[0077] The difference between Comparative Example 1 and Comparative Example 2 and Example 1 is that the deposition liquid of Comparative Example 1 contains no complexing agent, and the deposition liquid of Comparative Example 2 contains no complexing agent and Ti3C2T x From the data in Table 1, it can be seen that the corrosion resistance of the coatings prepared in Comparative Examples 1 and 2 is much lower than that in Example 1, and the performance comparison results of the three are: Comparative Example 2 < Comparative Example 1 < Example 1. The reason is that: Comparative Example 2 uses conventional electrodeposition to prepare the coating, and although Comparative Example 1 adds Ti3C2T x However, without a complexing agent, the deposition liquid agglomerates, which affects the electroplating effect. Figure 1 As can be seen in (d), the surface flatness of the coating obtained in Comparative Example 2 is very poor.

[0078] The difference between Comparative Example 3 and Example 1 is that an excessive amount of Ti3C2T x From the data in Table 1, it can be seen that the charge transfer resistance R ct Decrease, self-corrosion potential E corr Decrease, self-corrosion current density I corrIncrease; the overall corrosion resistance decreases.

[0079] The difference between Comparative Examples 4 and 5 and Example 1 is that the pH values ​​of the deposition solution during preparation are adjusted to 3 and 7 respectively. It can be seen from the data in Table 1 that the charge transfer resistance R ct Reduce the self-corrosion potential E corr Decrease, self-corrosion current density I corr Increase; that is, the overall corrosion resistance decreases.

[0080] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a two-dimensional composite corrosion-resistant coating of a neodymium iron boron magnet, characterized in that: The method comprises the following steps: Pre-treating the NdFeB magnets to obtain magnets with clean and rough surfaces to be electroplated; The magnet to be electroplated is immersed in a deposition solution, and a pulse electric field is applied to perform ion exchange electrodeposition, so that a two-dimensional composite coating is deposited on the surface of the magnet to be electroplated under the synergistic effect of electrostatic assembly and pulse electric field; The deposition solution includes a nickel-based electroplating solution, a complexing agent and a two-dimensional Ti3C2T x ; The complexing agent is selected from ammonia water, EDTA-2Na or ammonium citrate.

2. The method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet according to claim 1, characterized in that: The preparation method of the deposition solution is as follows: adding a complexing agent to a nickel-based electroplating solution, adjusting the solution pH to 4-6 after sufficient reaction, and then adding Ti3C2T x powder and dispersed it by ultrasonic to obtain a deposition solution.

3. The method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet according to claim 2, characterized in that: The two-dimensional Ti3C2T x The addition amount is 0.1g / L~0.3g / L.

4. The method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet according to claim 2, characterized in that: When the complexing agent is ammonia water, the dosage is 5ml / L to 20ml / L; when the complexing agent is EDTA-2Na or ammonium citrate, the dosage is 0.2g / L to 2g / L.

5. The method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet according to claim 2, characterized in that: The nickel-based electroplating solution comprises the following components in mass concentrations: 180 g / L to 280 g / L of nickel sulfate; 20 g / L to 40 g / L of nickel chloride; 30 g / L to 40 g / L of boric acid; and 0.05 g / L to 0.1 g / L of sodium dodecyl sulfate.

6. The method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet according to claim 1, characterized in that: The NdFeB magnet pretreatment specifically includes: First, place the NdFeB magnet in an alkaline cleaning solution at 65°C ± 5°C, stir to remove oil stains from the NdFeB magnet, and then clean it with water; the alkaline cleaning solution includes NaOH, Na2CO3, Na3PO4, an emulsifier and sodium dodecyl sulfate; Then soak the NdFeB magnet in HNO3 solution for 30s±5s, and then clean it with water; Then, the NdFeB magnet is immersed in the H2SO4 solution for 30s±5s, cleaned with water and then ultrasonically cleaned with anhydrous ethanol to obtain a magnet to be electroplated with a clean and rough surface.

7. The method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet according to claim 1, characterized in that: The parameters of ion exchange electrodeposition are: forward current density is 5A / dm 2 ~15A / dm 2 , operating frequency is 400Hz~1000Hz, duty cycle is 20%~60%; reverse current density is 0A / dm 2 ~1A / dm 2 , the operating frequency is 400Hz~1000Hz, and the duty cycle is 20%~60%.

8. The method for preparing a two-dimensional composite corrosion-resistant coating of a NdFeB magnet according to claim 7, characterized in that: The temperature of the ion exchange electrodeposition is 45°C±5°C.

9. A two-dimensional composite corrosion-resistant coating of NdFeB magnets obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for depositing Ni layer on surface of magnetic steel based on double-pulse technology

    CN111074305A